Monetary policy and the financial system - Horvitz, Paul M. (Englewood Cliffs, N.J.: Prentice-Hall, 1974)
The book examines monetary policy and the problem of achieving reasonable price stability with full employment. It also considers the challenges faced by the managers of financial institutions.
Includes
Includes bibliographical references and index.
usc 12/11/2018
Loans
Keywords: Monetary policy; Finance; United States